Possibilities of rehabilitation of the psychological state of children over 10 years old, suffering from acute respiratory diseases, in conditions of war in Ukraine - I.O. Mityuryayeva-Kornijko; Ie.A. Burlaka; T.D. Klets; O.A. Panchenko; A.V. Kabantseva; R.V. Terletskiy (Zdorovʹe Rebenka, 2025)
Background. Stressful conditions in children are often masked as somatic complaints like abdominal pain, cephalalgia, and nausea. An increase in these symptoms in stressful situations (for example, before an exam) indicates a possible psychosomatic nature of the complaints. Modern psychophysiological studies confirm that chronic stress leads to dysfunction of the autonomic nervous system, endocrine disorders and, as a result, somatic diseases. Prolonged stress can cause the development or exacerbation of diseases such as hypertension, cardiovascular disorders, diabetes, migraine, headache, respiratory diseases (bronchial asthma, frequent respiratory diseases), pathology of the gastrointestinal tract (ulcer disease, intestinal dysfunction). Stress is a powerful psychobiological factor that can significantly affect a child’s physical health. Therefore, early detection and correction of stressful conditions in children is an important task for preserving their health. This is a challenge for pediatric practice and requires improvement and increasing the effectiveness of rehabilitation measures, development of comprehensive therapeutic approaches. Aim: to increase the effectiveness of rehabilitation and treatment for psychological disorders in children over 10 years old with acute respiratory infections in the conditions of war in Ukraine through comprehensive pharmacological correction with the inclusion of immunocorrective and sedative agents. Materials and methods. The study included 123 children aged 10–18 years who during the previous year permanently lived in the territory of Ukraine (Kyiv, Kharkiv, Lviv, Dnipro, Zaporizhzhia, Odesa, Kropyvnytskyi, Vinnytsia, Kryvyi Rih, Zhytomyr, Cherkasy, Poltava, Sumy, Berdychiv, Romny, Bila Tserkva). The study was carried out as part of the program of outpatient observation of children with various acute manifestations of acute respiratory infections against the background of stress damage to the nervous system due to the war in Ukraine. They took naturopathic drugs with immunocorrective properties: affinity-purified antibodies to human interferon gamma (6 mg), histamine (6 mg) and CD4 (6 mg) — a mixture of homeopathic dilutions C12, C30 and C50 (scheme (1)) or in combination with a sedative: 1) affinity-purified antibodies to human interferon gamma (6 mg), histamine (6 mg) and CD4 (6 mg) — a mixture of homeopathic dilutions C12, C30 and C50 and 2) affinity-purified antibodies to brain-specific protein S100 (3 mg) — a mixture of homeopathic dilutions C12, C30 and C50 (scheme (1+2)). Statistical processing of the results was carried out using GraphPad Prism 9.0 Software for Windows (USA, San Diego, CA). Results. A comprehensive therapeutic regimen (1+2) has shown a significantly better effect on stress-related disorders, post-traumatic stress disorder, sleep disturbances, and quality of life. In addition, a more pronounced corrective and rehabilitative effect of scheme (1+2) was revealed on the indicators of fever, duration of low fever, sore throat, runny nose, symptoms of bronchitis, and manifestations of respiratory infection, assessed according to the Wisconsin Questionnaire. Analysis of satisfaction with the effect of treatment on the Integrative Medicine Outcome Scale during the observation period showed positive results and a high score when evaluated by parents and children. Conclusions. Thus, the synergy of rehabilitation for stress-related disorders and acute respiratory infections in school-age children under martial law in Ukraine with the use of immunocorrective and sedative agents has pronounced effects, both early and delayed, a high level of assessment by parents and children aged 10–18 years.